Hierarchical Power Allocation Control for Star-Connected Hybrid Energy Storage System Using Cascaded Multilevel Converters - Lu, Yiyan; Liu, Zhao; Lyu, Jianguo; Wei, Xing (Frontiers in Energy Research, 2021)
Hybrid energy storage system (HESS) using cascaded multilevel converters (CMC) has received increasing attention due to its merits on smoothing power fluctuations for renewable energy systems (RESs). However, CMC-based HESS still faces tough challenges due to asymmetrical ac power distribution. In this paper, hierarchical power allocation control strategy is utilized in CMC-based star-connected HESS to coordinate power between batteries and supercapacitors (SCs). Using the proposed power allocation mechanism, multi-modal energy management strategy (EMS) can be achieved, which includes normal operation mode and power compensation mode. In normal operation mode, SC voltages are regulated to achieve long-time stable operation. Power compensation mode aims to allocate the active power fluctuation and employs SCs to mitigate it. Meanwhile, the principle of the hierarchical power allocation strategy is analyzed to facilitate the accurate control and flexible switching of different operating modes. A series of simulation and experiment tests are executed to demonstrate the performance of the proposed control strategy.